Neuromyelitis optica spectrum disorders: A nationwide Portuguese clinical epidemiological study - Santos, E (2021)
Introduction: Neuromyelitis optica spectrum disorder (NMOSD) is a rare disorder in which astrocyte damage and/or demyelination often cause severe neurological deficits. Objective: To identify Portuguese patients with NMOSD and assess their epidemiological/clinical characteristics. Methods: This was a nationwide multicenter study. Twenty-four Portuguese adult and 3 neuropediatric centers following NMOSD patients were included. Results: A total of 180 patients met the 2015 Wingerchuk NMOSD criteria, 77 were AQP4-antibody positive (Abs+), 67 MOG-Abs+, and 36 seronegative. Point prevalence on December 31, 2018 was 1.71/100,000 for NMOSD, 0.71/100,000 for AQP4-Abs+, 0.65/100,000 for MOG-Abs+, and 0.35/100,000 for seronegative NMOSD. A total of 44 new NMOSD cases were identified during the two-year study period (11 AQP4-Abs+, 27 MOG-Abs+, and 6 seronegative). The annual incidence rate in that period was 0.21/100,000 person-years for NMOSD, 0.05/100,000 for AQP4-Abs+, 0.13/100,000 for MOG-Abs+, and 0.03/100,000 for seronegative NMOSD. AQP4-Abs+ predominated in females and was associated with autoimmune disorders. Frequently presented with myelitis. Area postrema syndrome was exclusive of this subtype, and associated with higher morbidity/mortality than other forms of NMOSD. MOG-Ab+ more often presented with optic neuritis, required less immunosuppression, and had better outcome. Conclusion: Epidemiological/clinical NMOSD profiles in the Portuguese population are similar to other European countries.